Redesign of stroller work tools at PT. Ika Bina Agro Wisesa - Syarifuddin, Syarifuddin; Akmal, Syarifah; Muetia, Sri; Ihsan, M. Rafiki; Nabila, Katiara Putri (Edelweiss Applied Science and Technology, 2024)
PT. Ika Bina Agro Wisesa (PT. IBAS) is one of the agro-industries that manages or produces palm oil with a production capacity of 30 tons / hour and a total of 420 tons / day. The raw material of Fresh Fruit Bunches (FFB) of this factory comes from the plantation land of the community around the factory. The activity of harvesting FFB in this oil palm plantation has many manual material handling activities, especially for workers who lift and push wheelbarrows (angkong). The angkong work tool used is relatively old and looks unergonomic which can be seen when pushing the angkong in a very bent position so it is assumed that there is a large amount of force expended by workers. This research begins with a survey of the company and the field, then distributing Nordic Body Map (NBM) questionnaires to workers, using the Rapid Entire Body Assessment (REBA) method used to determine the level of risk of work posture in workers before and after the design of the tool, for the redesign of the stroller, anthropometric measurements are taken then using the Biomechanics method to determine the amount of force generated when pushing. This stroller redesign was carried out using operator anthropometry with the 95th percentile. After using the proposed tool, the work posture assessment is categorized as moderate which means that action is needed. The final results of the redesign are the length of the cart 90 cm, the width of the cart 66 cm, the diameter of the tire 32 cm, the height of the cart from the ground 125 cm, the height of the handle 96 cm, the width of the handle 40 cm, and the diameter of the handle 3 cm and the final results of the biomechanical assessment after the design concluded that the operator was no longer dangerous when pushing.